P535 COVID-19 vaccine-induced neutralising antibody responses against SARS-CoV-2 Omicron BA.4/5 are diminished in patients with inflammatory bowel disease on anti-TNF or JAK-inhibitor therapy. (30th January 2023) - Liu, Z; Alexander, J; Le, K; Zhou, X; Ibraheim, H; Anandabaskaran, S; Saifuddin, A; Lin, K; Mcfarlane, L; Anand, N; Constable, L; Castro-Seoane, R; et al.
Abstract: Background: Patients with Inflammatory bowel disease (IBD) receiving anti-TNF or JAK-inhibitor therapy have attenuated responses to COVID-19 vaccination. We aimed to determine how IBD treatments affect neutralising antibody responses against the currently dominant Omicron BA.4/5 variants. Methods: We prospectively recruited 329 adults (68 healthy controls (HC) and 261 IBD) who had received three doses of COVID-19 vaccine at nine UK centres. The IBD population was established (>12 weeks therapy) on either thiopurine (n=60), infliximab (IFX) (n=43), thiopurine & IFX combination (n=46), ustekinumab (n=43), vedolizumab (n=46) or tofacitinib (n=23). Pseudoneutralisation assays were performed and the half maximal inhibitory concentration (NT50) of participant sera was calculated. The primary outcome was anti-SARS-CoV-2 neutralising response against wild-type (WT) virus and the BA.4/5 variant after the second and third doses of anti-SARS-CoV-2 vaccine, stratified by immunosuppressive therapy, adjusting for prior infection, ethnicity, vaccine type and age. Results: Heterologous (two doses adenovirus vaccine, third dose mRNA vaccine) and homologous (three doses mRNA vaccine) vaccination strategies significantly increased neutralising titres against both WT SARS-CoV-2 virus and the BA.4/5 variants in HCs and IBD (fig 1). Antibody titres against BA.4/5 were significantly lower than antibodies against WT virus in both groups (Geometric Mean Ratio (GMR) [95% CI], 0.11 [0.09, 0.15], P<0.0001 in healthy participants; GMR 0.07 [0.06, 0.08], P<0.0001 in IBD patients). Multivariable models showed that neutralising antibodies against BA.4/5 after three doses of vaccine were significantly lower in IBD patients on IFX (GMR 0.44 [0.20, 0.97], P=0.042), IFX and thiopurine combination (GMR 0.34 [0.15, 0.77], P=0.0098) or tofacitinib (GMR 0.37 [0.15, 0.92], P=0.032), but not in patients on thiopurine monotherapy, ustekinumab or vedolizumab. Breakthrough infection was associated with lower neutralising antibodies against WT and BA.4/5 (P<0.05). Conclusion: A third dose of COVID-19 vaccine based on the WT spike glycoprotein boosts neutralising antibody titres in patients with IBD. However, responses are lower against the currently dominant variant BA.4/5, particularly in patients taking anti-TNF or JAK-inhibitor therapy. Breakthrough infections are associated with lower neutralising antibodies and immunosuppressed IBD patients may receive additional benefit from bivalent vaccine boosters which target Omicron variants. Financial support was provided as an Investigator Sponsored Research Grant from Pfizer Limited.